Novel gas sensing mechanisms of Pd and Rh-doped h-BN monolayers for detecting dissolved gases (H2、CH4、and C2H4) in transformer oil - Jiang, Jiaming; Yang, Dingqian; Zeng, Wen; Wang, Zhongchang; Zhou, Qu (Frontiers in Chemistry, 2024)
Abstract：Detecting dissolved gases in transformer oil is crucial for assessing the operational status of transformers. The gas composition in transformer oil can reflect the health status of the equipment and help identify potential failure risks in a timely manner. Based on density functional theory (DFT), the sensing performance of H2, CH4, and C2H4 gases on Pd-doped and Rh-doped h-BN monolayers are analyzed. The results indicate that Pd-BN and Rh-BN exhibit enhanced sensitivity to H2 and C2H4 gases compared to pristine h-BN. However, they show poor adsorption characteristics for CH4. Both Pd-BN and Rh-BN demonstrate strong chemisorption for H2 and C2H4. In contrast, CH4 adsorption is predominantly physisorbed. The desorption time of H2 from Pd-BN at 398K is 164 seconds, reflecting its excellent desorption performance.Additionally, Pd-BN and Rh-BN monolayers exhibit exceptional C2H4 capture capabilities, with adsorption energies of -1.697 eV and -2.188 eV, respectively, indicating their potential as C2H4 gas adsorbents. These findings provide theoretical insights for selecting materials for dissolved gas detection in oil and lay the groundwork for the development of Pd-BN and Rh-BN-based gas sensors.